A novel hyaluronidase from brown spider (Loxosceles intermedia) venom (Dietrich's Hyaluronidase): from cloning to functional characterization. - Valéria Pereira Ferrer; Thiago Lopes de Mari; Luiza Helena Gremski; Dilza Trevisan Silva; Rafael Bertoni da Silveira; Waldemiro Gremski; Olga Meiri Chaim; Andrea Senff-Ribeiro; Helena Bonciani Nader; Silvio Sanches Veiga (Public Library of Science (PLoS), 2013)
Loxoscelism is the designation given to clinical symptoms evoked by Loxosceles spider's bites. Clinical manifestations include skin necrosis with gravitational spreading and systemic disturbs. The venom contains several enzymatic toxins. Herein, we describe the cloning, expression, refolding and biological evaluation of a novel brown spider protein characterized as a hyaluronidase. Employing a venom gland cDNA library, we cloned a hyaluronidase (1200 bp cDNA) that encodes for a signal peptide and a mature protein. Amino acid alignment revealed a structural relationship with members of hyaluronidase family, such as scorpion and snake species. Recombinant hyaluronidase was expressed as N-terminal His-tag fusion protein (∼45 kDa) in inclusion bodies and activity was achieved using refolding. Immunoblot analysis showed that antibodies that recognize the recombinant protein cross-reacted with hyaluronidase from whole venom as well as an anti-venom serum reacted with recombinant protein. Recombinant hyaluronidase was able to degrade purified hyaluronic acid (HA) and chondroitin sulfate (CS), while dermatan sulfate (DS) and heparan sulfate (HS) were not affected. Zymograph experiments resulted in ∼45 kDa lytic zones in hyaluronic acid (HA) and chondroitin sulfate (CS) substrates. Through in vivo experiments of dermonecrosis using rabbit skin, the recombinant hyaluronidase was shown to increase the dermonecrotic effect produced by recombinant dermonecrotic toxin from L. intermedia venom (LiRecDT1). These data support the hypothesis that hyaluronidase is a "spreading factor". Recombinant hyaluronidase provides a useful tool for biotechnological ends. We propose the name Dietrich's Hyaluronidase for this enzyme, in honor of Professor Carl Peter von Dietrich, who dedicated his life to studying proteoglycans and glycosaminoglycans.